C-Peptide in Beta Cell Regeneration and Autoimmune Diabetes: A Therapeutic Perspective - Dhoundiyal, Shivang (Glucolipid Metabolic Disorders, 2025)
In autoimmune diabetes, the body's immune system attacks and destroys pancreatic beta cells, leading to a complete loss of insulin production. As a result, individuals with this condition require lifelong external insulin therapy. Recent advancements in diabetes treatment have focused on strategies to preserve and regenerate beta cell mass, making this an important area for research. Beyond its role in insulin biosynthesis, C-peptide has gained attention for its physiological effects, which extend beyond simply being a byproduct of insulin production. This review explores the structure and function of C-peptide, its potential impact on autoimmune processes in Type 1 diabetes, and its ability to stimulate beta cell regeneration. Additionally, we discuss the mechanisms by which C-peptide protects beta cell function, counteracts the harmful effects of pro-inflammatory cytokines, and modulates immune responses. Clinical trials have provided promising evidence that C-peptide supplementation can lead to improved clinical outcomes, including enhanced insulin secretion, better beta cell function, and a reduction in diabetes-related complications. This article also examines the potential for C-peptide therapy to become a standard treatment option for autoimmune diabetes, either as a standalone therapy or in combination with other treatments aimed at modulating the immune system and promoting beta cell regeneration. By providing insights into the multiple therapeutic roles of C-peptide, this review aims to help readers understand its potential as a valuable tool in diabetes management and its broader implications for controlling autoimmune diabetes.
Keywords: hyperglycemia